(untitled) (Global Journal of Management and Business Research, 2021)
Policy transfer has been the dominant approach by donors to domestic policy development in less developed countries across Africa. Arguably, countries in the global north have been the main sources and triggers of public sector reforms to Africa. Many of the reforms, were inspired by the ideas of New Public Management (NPM) and e-government strategies. The nature of the transfer has been partly imposed due to loan, debt relief, and technological dependence on the global north by the Nigerian Government. The donors that trigger such transfers in many cases ignored the domestic contextual factors and the critical role of Street- Level-Bureaucrates in policy implementation in developing countries. But the use of conditions by donors to impose policy on African governments may not necessarily lead to the expected outcomes of policy implementation. The Nigeria Immigration Service was used as an empirical case in this research. The data for this study was collected through the use of in-depth interviews with relevant governmental and non-governmental policy actors and documentary sources.